(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Sustainable development involves resource preservation and development. Sustainable development meets the requirements of current and future generations evenly. Sustainable tourism research and development are still relevant in an uncertain and complicated global world. The Otlier test determined whether data might disturb the following analysis strategy. If the minimal sample assumption holds, exclude outlier data. This study will screen participants beyond 10% of the planned minimum sample data limit. Standard factor loadings in individual measurement models exhibit impairment but stabilize at 0.60 or higher. Hence, the observed items measure latent variables in independent and dependent constructs consistently and significantly. Standard factor loadings in individual measurement models exhibit impairment but stabilize at 0.60 or higher. Hence, the observed items measure latent variables in independent and dependent constructs consistently and significantly. Standard factor loadings in individual measurement models exhibit impairment but stabilize at 0.60 or higher. Hence, the observed items measure latent variables in independent and dependent constructs consistently and significantly